Sensitivity of Sexual Victimization Estimates to Definitional and Measurement Decisions - Krebs, Christopher (Journal of interpersonal violence, 2021)
Self-report surveys are subject to measurement error associated with variation in the methodology employed. The current analysis uses data from the Campus Climate Survey Validation Study (CCSVS) to examine the impact that measurement decisions have on estimates. The findings demonstrate that asking victims to provide detailed information in an effort to properly place incidents in time and classify incidents by type resulted in relatively minor decreases in estimate magnitude. Ultimately, asking respondents to provide or confirm additional incident-level information for proper classification resulted in more complete information with very little impact on estimates.